Integrasi Nilai PAI untuk Mendorong Kesetaraan Gender dan Penghargaan terhadap Perbedaan - Anis Khoeriah; Zumrotus Sholikah; Salmi Nelsya (Journal of Humanities, Social Sciences, and Education, 2025)
This literature study aims to analyze the integration of Islamic Religious Education (PAI) values ​​in promoting gender equality and respect for differences in the educational context. Amidst growing global awareness of the importance of social justice, PAI plays a strategic role as a subject that not only teaches ritual aspects but also shapes students' character and social behavior. The literature shows that Islamic values ​​such as al-musāwah (equality), ‘adālah (justice), rahmah (compassion), and respect for diversity are relevant normative foundations in PAI learning to build a moderate, inclusive, and just perspective. This study identifies several implementation strategies, such as integrating equality values ​​into morals materials, using a pedagogical approach that emphasizes collaboration without gender bias, and developing a school culture that upholds anti-discrimination. The study also reveals that implementation barriers still arise, such as patriarchal culture, teachers' lack of understanding of the concept of gender in Islam, and resistance from some communities who consider gender issues to be a Western product. However, studies have concluded that integrating Islamic Religious Education (PAI) values ​​into gender issues can increase mutual respect, reduce gender stereotypes, and strengthen tolerance in educational settings. This literature review recommends strengthening teacher competencies, updating the Islamic Religious Education (PAI) curriculum to be based on equality, and collaboration between schools and families to build an inclusive learning environment.